2018
DOI: 10.1101/497073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic reconstruction and divergence time estimation of Blumea DC. (Asteraceae: Inuleae) in China based on nrDNA ITS and cpDNA trnL-F sequences

Abstract: 1 5

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The alignments were used for phylogenetic analysis. After that, according to the method described by Xie et al [55] and Zhang et al [56], we used four methods to construct phylogenetic trees: NJ method, MP method, BI method and ML method. Coffea canephora and Coffea arabica were selected as the outgroup.…”
Section: Phylogenetic Analysis Of Camelliamentioning
confidence: 99%
“…The alignments were used for phylogenetic analysis. After that, according to the method described by Xie et al [55] and Zhang et al [56], we used four methods to construct phylogenetic trees: NJ method, MP method, BI method and ML method. Coffea canephora and Coffea arabica were selected as the outgroup.…”
Section: Phylogenetic Analysis Of Camelliamentioning
confidence: 99%
“…The alignments were used for phylogenetic analysis. According to the method described by Xie et al [53] and Zhang et al [54], we used four methods to construct phylogenetic trees, that were the NJ method, the MP method, the BI method and the ML method. Coffea canephora and Coffea arabica were selected as the outgroup.…”
Section: Phylogenetic Analysis Of Camelliamentioning
confidence: 99%
“…Previous phylogenetic studies had revealed that Blumea is a sister group of the genus Caesulia Roxb. (Anderberg et al 2005 ; Pornpongrungrueng et al 2007 ; Zhang et al 2019 ). Combining evolutionary information of the ITS, trnL-trnF , and trnH-psbA regions from 30 Blumea species, Pornpongrungrueng et al ( 2007 , 2009 ) were the first to examine the infrageneric relationships of Blumea and identified three clades in the genus–– B. lacera clade, B. densiflora clade, and B. balsamifera clade.…”
Section: Introductionmentioning
confidence: 99%
“…Their phylogeny showed that the relationships among the three clades were unresolved and pointed out that several taxa were not monophyletic. Zhang et al ( 2019 ) investigated the infrageneric relationships of 22 Chinese Blumea taxa with the ITS and trnL-trnF regions, recognized two clades. The clade I, which contained B. densiflora clade and B. balsamifera clade recognized by Pornpongrungrueng et al ( 2007 , 2009 ), however, had low supports in Zhang et al ( 2019 ) phylogenies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation